2023
DOI: 10.1007/s10457-023-00899-z
|View full text |Cite
|
Sign up to set email alerts
|

Towards indigenous community-based adaptation to climate change: a typological analysis of tree-livestock integration in smallholding systems in dryland areas of Benin (West-Africa)

Alassan S. Assani,
Amoudawenou Koara Yarou,
Nadège V. F. G. Dedehou
et al.

Abstract: Integration of livestock farming practices with trees is neglected and poorly explored in the context of climate change (CC) in drylands. However, such knowledge is urgently needed to propose effective strategies in the livestock sector to cope with CC. This study is initiated to characterize the diversity of indigenous integrated livestock systems with trees in drylands of Benin through a survey including 140 smallholder farmers. Data were submitted to a multiple correspondence analysis with hierarchical asce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Dairy farmers of these regions are known for their practice of adaptation to CC based on the integration of animals with trees or shrubs. The herds of farmers who participated in this study were those who had at least two cows at the early lactation and who had participated in the previous study initiated by Assani et al (2023). The previous study identified four types of smallholder dairy cattle farms namely traditional silvopasture (TSS); Improved Silvopasture (ISS); Small-scale Agrosilvopasture (SIAS) and Large Integrated Agrosilvopasture (LIAS).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Dairy farmers of these regions are known for their practice of adaptation to CC based on the integration of animals with trees or shrubs. The herds of farmers who participated in this study were those who had at least two cows at the early lactation and who had participated in the previous study initiated by Assani et al (2023). The previous study identified four types of smallholder dairy cattle farms namely traditional silvopasture (TSS); Improved Silvopasture (ISS); Small-scale Agrosilvopasture (SIAS) and Large Integrated Agrosilvopasture (LIAS).…”
Section: Study Areamentioning
confidence: 99%
“…The previous study identified four types of smallholder dairy cattle farms namely traditional silvopasture (TSS); Improved Silvopasture (ISS); Small-scale Agrosilvopasture (SIAS) and Large Integrated Agrosilvopasture (LIAS). The characteristics of the four identified type of farmers in dryland areas of Benin are presented in Supplementary Table S1 (Assani et al, 2023). In TSS, farmers had an average of 26 Tropical Livestock Unit (TLU).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Farmers adopted various coping strategies to deal with climate disturbances and anthropic pressure. These strategies vary according to their prosperity level and economic resources [9,10]. Improving traditional pastoralism systems is needed as an adaptation and mitigation strategy to be used by smallholder farmers in Benin [10].…”
Section: Introductionmentioning
confidence: 99%
“…These strategies vary according to their prosperity level and economic resources [9,10]. Improving traditional pastoralism systems is needed as an adaptation and mitigation strategy to be used by smallholder farmers in Benin [10]. Small ruminants are kept on small-scale farms and play an important role in the livelihood strategies of resource-poor farmers [11,12], including income generation, insurance (sale for cash to meet unexpected expenditures), economic Sustainability 2024, 16, 2270 2 of 15 security (sale for cash to support foreseeable expenses), social/religious functions, and prestige in ownership [13].…”
Section: Introductionmentioning
confidence: 99%